(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
This study aimed at studying the effect of five volatile plant oils namely; Mentha piperita (Peppermint), Origanum marjorana (Marjoram), Plargonium graveolens (Geranium), Cymbopogon proxiomus (Lemongrass) and Ocimum basilicum (Basil), were used at different concentrations (0.625, 1.25, 2.50 and 5.00%) against the Greater wax moth, Galleria mellonella. Also, the combined effect of both gamma irradiations with the dose levels 0,100 and 150 Gy and the volatile oils were investigated against this pest. The results obtained showed that the percentage of the population was significantly decreased by increasing the concentration in most treatments. Adult emergence and sex ratio were fluctuated unmatched with the applied dose levels. The survival percentage was inversely correlated with the increase in concentration. Also the average larval and pupal period significantly increased among all concentrations at all treatments compared with the control treatment. High bioactivity of the botanical oils and gamma-irradiation doses against the Greater wax moth, Galleria mellonella, such results may offer an opportunity for developing alternatives to rather expensive and environmentally hazardous organic insecticides.